The influence of bile salt on the chemotherapeutic response of docetaxel-loaded thermosensitive nanomicelles - Kim, Dong Wuk (Dove Medical Press, 2014)
The primary aim of this work was to investigate the potential of bile salt, sodium taurocholate (NaTC), in improving the bioavailability and anti-tumor efficacy of docetaxel (DCT) upon rectal administration. Poloxamer-based nanomicelles with thermosensitive and mucoadhesive properties were prepared using the cold method. The optimized nanomicellar formulation was evaluated in terms of physicochemical and viscoelastic parameters. Nanomicelles containing bile salt maintained sufficient gelation strength (234×10(2) mPa·s) and mucoadhesive force (17.3×10(2) dyne/cm(2)) to be retained in the upper part of the rectum. They significantly enhanced the DCT internalization across the rectal mucosa and showed a high plasma level during the first 4 hours of the study period, compared to nanomicelles with no bile salt. As a result, a slightly higher rectal bioavailability of ~33% was observed in nanomicelles containing bile salt, compared to ~28% from the latter system. The higher pharmacokinetic parameters for rectally administered DCT/P407/P188/Tween 80/NaTC (0.25%/11%/15%/10%/0.1% by weight, respectively) resulted in significant anti-tumor efficacy. However, the tumor regression rate for the NaTC group was not statistically different from that for nanomicelles without NaTC. Therefore, overall results suggest that thermosensitive nanomicelles could be a potential dosage form for improvement of the bioavailability and chemotherapeutic profile of DCT.